PENGARUH PENGETAHUAN, PENDIDIKAN DAN SIKAP IBU DENGAN PEMBERIAN IMUNISASI HEPATITIS B PADA BAYI 0-7 HARI DI WILAYAH KERJA PUSKESMAS PEMURUS BARU BANJARMASIN - Kusumawati, Sixtia; Lestari, Nur Cahyani Ari; Novembriany, Yerika Elok (Universitas Batam, 2021)
According to WHO, about 30% or 350 million of the world's population shows positive symptoms of Hepatitis B and the Southeast Asia region is an area with a high endemic rate, while Indonesia is a country with a medium to high endemic level with 11 million sufferers. Hepatitis B immunization coverage in South Kalimantan is still lacking, namely 47,762 people (70.6%) and the coverage of hepatitis B immunization 0-7 days at Pemurus Baru Health Center is 198 people (37.9%) even though the target set by the Government is 80%. The aim of this research is to know the description of mother's knowledge, education and attitudes regarding the administration of Hepatitis B Immunization for Infants 0-7 days. The research design used descriptive method. The population is all mothers who have babies 1-12 months in the Working Area of Pemurus Baru Health Center with a sample of 30 people. Taken by accidental sampling technique. The results of this study were that the respondents who were given Hepatitis B immunization 0-7 days were 17 people (60%) and those who were not given were 13 people (40%). Good knowledge 4 people (13%), enough 4 people (13%) and less than 22 people. Basic education 19 people (63%), middle school 7 people (23%) and high school 4 people (14%). Positive attitude 14 people (47%) and negative 16 people (53%). The conclusion of this study is that 17 people (60%), 22 people (74%), 19 people with basic education (63%) and 16 people (53%).